2014
DOI: 10.3171/2013.9.spine121136
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol, a selective Type III phosphodiesterase inhibitor: prevention of cervical myelopathy in a rat chronic compression model

Abstract: These results indicate that cilostazol is neuroprotective in the chronically compressed cervical cord and is potentially useful in the treatment of cervical spondylotic myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…16,17 However, the studies did not achieve treatment effects on the progression of compression myelopathy. The present study demonstrated that G-CSF could have promising potential as a treatment to restore developing compression myelopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 However, the studies did not achieve treatment effects on the progression of compression myelopathy. The present study demonstrated that G-CSF could have promising potential as a treatment to restore developing compression myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The rotation speed was set at 10 rpm based on our previous reports. 2,16,17 Before surgery, all rats could walk continuously for more than 300 seconds. Therefore, we set a cut-off of 300 seconds, and latency to fall off the rotarod was measured before and after surgery.…”
Section: Rotarod Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Existing models mimicking chronic cord compression in rats include insertion of expandable polymers [50], adjustable screws [33], and calcification-inducing polymers [28]. These result in loss of neurons, predominantly in the grey matter of the ventral horns at the lesion epicentre.…”
Section: Introductionmentioning
confidence: 99%
“…Preferential neuronal loss has also been demonstrated in canine screw compression models [21] and twy-twy mouse models [1]. In addition, demyelination has been observed in some CSM models [28, 51], although myelin pallor or frank myelin loss is not generally present in expandable polymer animal models [30, 50]. …”
Section: Introductionmentioning
confidence: 99%